A política de assistência social brasileira no contexto do capitalismo contemporâneo financeirizado: uma análise do período 2003 a 2010 - Justo, Rafael Breda (2017)
Starting in 2003, with Lula's entry into the Presidency of the Republic, the social assistance policy passes as the main way of dealing with social problems in Brazil. The expansion of this policy in the period, mostrly through the prioritization of policies related to the mechanisms of income transfer, permeate the debate about social policies and served mainly as a defense instrument of that government. The understanding over the outline of the social assistance policy implemented in the period from 2003 to 2010 has a very close relation with the context of the contemporary accumulation model, based on the process of financerization of the economies, by the logic of the economic policy implemented from the 1990s and consolidated from the establishment of the Real Plan.In this sense, the main objective of this research is to analyze a policy of Brazilian assistance in the period from 2003 to 2010 taking into account its dialectical relationship with the context of hegemony of the contemporary capital accumulation model